(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The empirical investigation intended to make a comparison amongst youths belonging to urban, semi-urban and rural areas in terms of achievement related behavioural orientations, goal setting, risk-taking behaviour, social mobility, perceived education employment link and perceived effort-outcome link. It was hypothesized that educated youths from urban, semi urban and rural areas would differ significantly from among themselves in terms of (i) goal setting, (ii) risk-taking behaviour, (iii) social mobility, (iv) PEEL and (v) PEOL respectively. For the purpose youths of urban (N = 120), semi-urban (N = 140) and rural (N = 220) areas were administered Achievement Behaviour Questionnaire (ABQ) along with PDS to measure the variables and to seek their personal information. The obtained data were analysed using t-test. The hypotheses were retained. It was found that educated urbanized youth excelled over semi-urban youth and semi urban youth excelled over rural youth in terms of achievement related behavioural orientations namely goal setting, risk-taking behaviour, social mobility, perceived education employment link and perceived effort outcome link respectively. Thus, it is concluded that achievement related behavioural orientations are the function of inhabitation.